Systematic review with meta‐analysis: the long‐term efficacy of Barrett's endoscopic therapy—stringent selection criteria and a proposal for definitions. Issue 3 (24th June 2021) - Desai, Madhav; Rösch, Thomas; Sundaram, Suneha; Chandrasekar, Viveksandeep Thoguluva; Kohli, Divyanshoo; Spadaccini, Marco; Hassan, Cesare; Repici, Alessandro; Sharma, Prateek
Summary: Background: Barrett's endoscopic therapy (BET) is well established for neoplasia in Barrett's oesophagus using a concept of complete eradication of all Barrett's. However, long‐term efficacy is not known. Aims: To perform a systematic review and meta‐analysis to examine long‐term efficacy of BET for Barrett's neoplasia. Methods: Electronic databases were searched for studies meeting stringent criteria: (a) subjects with high‐grade dysplasia and/or superficial adenocarcinoma who underwent BET (ablation ± endoscopic mucosal resection); (b) BET completion by confirmation of complete eradication of neoplasia (CE‐N) and intestinal metaplasia (CE‐IM) with systematic sampling and (c) clearly defined follow‐up (endoscopy and biopsy) protocol of ≥2 years thereafter for detection of recurrence. Pooled estimates of CE‐N and CE‐IM after BET completion and follow‐up were analysed. Results: Eight studies met the stringent criteria (n = 794, males 89%, age 64.6 years). Despite high efficacy of BET at therapy completion (CE‐N: 95.9 [91.7‐98.7]%; CE‐IM: 90.9 [83‐96.6]%), this declined (CE‐N: 89 [73.4‐98.2]%; CE‐IM: 77.8 [65.6‐88]%) over 3.4 years of follow‐up. There was considerable heterogeneity. Only two studies reported a post‐BET follow‐up of >5 years (CE‐IM 50 [41.5%‐58.5]%). Higher person years of follow‐up seem to correlate with decrease in BET efficacy. Conclusion: Using stringent criteria for appropriate study selection with sufficient follow‐up, a lack of high‐quality controlled intervention trials becomes evident for assessment of long‐term durable remission rates of BET despite initial high success rates. We plea for a uniform documentation of study details which could be used in future trials. Abstract : Lack of high‐quality, long‐term efficacy data. 78% sustain Barrett's remission over 3.4 years.